2019
DOI: 10.1038/s41598-019-46115-w
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of melanoma by blue-light photoactivation of flavin mononucleotide

Abstract: Melanoma is one of the most aggressive and lethal form of cancer. Photodynamic therapy (PDT) is a clinically approved technique for cancer treatment, including non-melanoma skin cancer. However, the most of conventional photosensitizers are of low efficacy against melanoma due to the possible dark toxicity at high drug concentrations, melanin pigmentation, and induction of anti-oxidant defense mechanisms. In the current research we propose non-toxic flavin mononucleotide (FMN), which is a water-soluble form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 50 publications
1
67
0
Order By: Relevance
“…Although melanoma is a rare kind of tumor, it is one of the highly aggressive and lethal cancers with a mortality rate of 80% of the total number of skin cancers due to its high metastasis and acquired chemoresistance. 2,27 The primary treatments of melanoma are surgery, chemotherapy and radiotherapy, of which may face the dilemma of limited treatment ranges and serious side effects. 2 However, skin melanoma also shows the ability of light illuminate, making PDT a promising treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although melanoma is a rare kind of tumor, it is one of the highly aggressive and lethal cancers with a mortality rate of 80% of the total number of skin cancers due to its high metastasis and acquired chemoresistance. 2,27 The primary treatments of melanoma are surgery, chemotherapy and radiotherapy, of which may face the dilemma of limited treatment ranges and serious side effects. 2 However, skin melanoma also shows the ability of light illuminate, making PDT a promising treatment.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, PDT can further prevent tumor recurrence by stimulating the body's immune system to produce tumor immune memory. 27 Furthermore, the combination of traditional treatments and PDT can further reduce drug use and avoid potential side effects while ensuring efficacy. Unlike photothermal agents that have both elevated temperatures and the ability to generate singlet oxygen, [29][30][31] photosensitizers are generally considered to have only the ability to produce singlet oxygen unless they possess particular morphological features.…”
Section: Discussionmentioning
confidence: 99%
“…HaCat [44] and A375 [45] cells are known for their high expression of EGFR while, in contrast, B16F10 cells express low levels of this receptor [46]. Furthermore, the three cell lines have been associated with the presence of CD44 membrane receptors [47], with the lowest expression in HaCat cells and the highest in B16F10 cells. Cell lines were grown in DMEM with glucose (4500 mg/L), supplemented with 10% FBS and 100 IU/mL penicillin and 100 µg/mL streptomycin (Invitrogen; complete medium).…”
Section: In Vitro Safety Assays On Hacat A375 and B16f10 Cell Linesmentioning
confidence: 99%
“…For melanoma, PDT has had limited success, and resistance to PDT has been observed (223). A recent study demonstrated that flavin mononucleotide, which is a water‐soluble form of riboflavin (vitamin B 2 ), selectively accumulated in melanoma cells and suppressed tumor growth in a mouse xenograft model (224).…”
Section: Prevention and Treatment Of Nonmelanoma Skin Cancermentioning
confidence: 99%